ESTIMATION FOLLICULAR FLUID CONTENTS AND SERUM IN AGEING IRAQI WOMEN-DURING IVF/ICSI CYCLES - Tiba Adnan K.; Lina A. Salih (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was aimed to estimate the effects of women age on oocytes quantity and quality and to determine whether there is a correlation between serum and follicular hormone levels. The samples were collected in the higher institute for the diagnosis of infertility and assisted reproduction techniques, Baghdad, Iraq. The 60 participants were split into two age groups, G1involved women younger than 35, while G2 involved women older than 35 years of age. The levels of FSH, LH, AMH, and GH in the serum and follicular fluid (FF) could be measured using (ELISA). The results demonstrated differences in the serum levels of FSH, LH, AMH, and GH between the young and elderly groups of infertile women on the day of oocyte extraction. The results proved statistically highly significant (P≤0.01) drop in the mean levels of hormones in the aged women group (FSH 21.67±0.53; LH 62.12±0.54; AMH 1370.74±94.59; GH 9.76±0.32 mIU/ML) compared with the younger women group (FSH 33.86±0.72; LH 85.072±2.70; AMH 3310.92±83.87; GH 30.40±0.45 mIU/ML). in this study the level of studied hormones in FF were significantly decreased with increasing women age, the mean of (FSH 19.59 ±0.28; LH 63.34 ±0.27; AMH 1769.46 ±17.92; GH 7.86 ±027 mIU/ML) in comparison with those levels in the younger group (FSH 31.40 ±0.95; LH 95.07 ±2.58; AMH 2547.35 ±124.09; GH 23.33 ±0.67 mIU/ML).